Namibië drie jaar later: politiek ontvoogd maar economisch wankel - Willemot, Yves (Afrika Focus, 1992)
Namibia became independent on the 21st of March 1990, after seventy-five years of South African colonial and racial rule. SWAPO fought a long war for liberation, but the independence was also gained thanks to the diplomatic pressure from the United Nations. The United Nations were actively involved in the organisation of the first free elections which were held on the 7th of November 1989. The SWAPO liberation movement became by far the most important political party in the Namibian Parliament. But from the beginning the SWAPO-leaders explained that the past should be forgotten. They promoted a constructive political and economic collaboration with all Namibians, African and European. Due to this atmosphere of reconciliation Namibia had a successful political independence. One of the world's most progressive constitutions was written. It ends all racial discrimination and guarantees an extensive review of the human rights. The rules for the organisation of the legislative, executive and judiciary power are respected by all political parties. Namibia is without any doubt an example for a lot of African countries, which are now making steps towards democracy and multi-partyism. The Namibian government has still a lot of problems to deal with. The major ones are the social and economic inequalities that still exist between African and European Namibians. The conditions of life of the European Namibians are comparable to these in modern western societies, while African Namibians are living in poverty. The government will have to change this, because in the long term one cannot expect to build democracy on empty stomachs. But in order to realize the necessary economic growth, Namibians are also counting on the support and the investments from abroad. A member of government recently said: "Now we've installed democracy and the human rights are respected, where are the foreign in- vestments and the international aid?"